Effectiveness of Self Management Technique Intervention in Reducing Addictive Behavior towards Online Games in Adolescents: A Literature Study - Novida Nurhayati; Muta Ali Arauf; Budi Purwoko (International Journal of Social Science and Religion (IJSSR), 2023)
Generally, the handling of online game addiction in adolescents is still dominated by conventional counseling interventions, even though along with the rapid development of science there are many alternative interventions that can be applied in handling internet addiction in adolescents. One of them is intervention with self management techniques in recent years began to be widely used for handling online game addiction. Therefore, this study intends to examine and map the use of self management technique interventions in reducing adolescent online game addiction behavior. Through a literature study, the researcher tries to compile, analyze, and present the study material systematically in accordance with the research objectives. The results of the study of the ten articles analyzed, the researcher concluded that efforts to improve self-management in adolescents are effective to suppress and prevent addiction from getting worse, as well as self-management interventions proven effective in reducing online game addiction, and have a positive impact on adolescent mental health. Therefore, school counselors need to learn and practice self-management-based interventions in an effort to deal with online game addiction gradually.